2017
DOI: 10.1038/aps.2016.153
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 and CTLA4 gene polymorphisms may influence the tacrolimus dose requirement in Chinese kidney transplant recipients

Abstract: The highly variable pharmacokinetics and narrow therapeutic window of tacrolimus (TAC) has hampered its clinical use. Genetic polymorphisms may contribute to the variable response, but the evidence is not compelling, and the explanation is unclear. In this study we attempted to find previously unknown genetic factors that may influence the TAC dose requirements. The association of 105 pathway-related single nucleotide polymorphisms (SNPs) with TAC dose-adjusted concentrations (C0/D) was examined at 7, 30 and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…Although the primary role of tacrolimus in this setting is to prevent GVHD, we were unable to accurately depict the impact of pharmacogenetics or drug exposure on incidence of GVHD because patients received other immunosuppressants such as cyclophosphamide or mycophenolate mofetil post-transplant. Additionally, other genetic polymorphisms (eg, PXR, POR, as well as others) [18,[36][37][38] are not accounted for in this study, which could possibly explain some of the observed variability in i.v. tacrolimus exposure among this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary role of tacrolimus in this setting is to prevent GVHD, we were unable to accurately depict the impact of pharmacogenetics or drug exposure on incidence of GVHD because patients received other immunosuppressants such as cyclophosphamide or mycophenolate mofetil post-transplant. Additionally, other genetic polymorphisms (eg, PXR, POR, as well as others) [18,[36][37][38] are not accounted for in this study, which could possibly explain some of the observed variability in i.v. tacrolimus exposure among this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The only difference between the two compounds was that they possessed a different substituted group in C-9. The 1 H NMR signals at δ H 2.11 (3H, s) and 13 C NMR signals at δ C 170.8 showed the presence of acetoxy group in 2. HMBC correlations (Figure 3) of H-9 (δ H 4.52) with C=O (δ C 170.8), and of the methyl at δ H 2.11 (3H, s) with C=O at δ C 170.8 confirmed the acetoxy group was located at C-9.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, five new dibenzocyclooctadiene lignans [12,13] and a new triterpenoid [14] from the stems of Kadsura renchangiana indigenous to southern area of China have been reported. Our further investigation on the same plant led to the isolation and identification of two new sesquiterpenoids, renchangianins F and G (1 and 2, Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P450 (CYP) 3A4 is the most abundant metabolic enzyme in liver, and in vivo CYP3A4 activity was found to explain an additional 23% to 29% of the variability of tacrolimus pharmacokinetics . A number of CYP3A4 polymorphisms were found to affect the expression and activity of CYP3A4 enzyme as well as tacrolimus pharmacokinetics, including CYP3A4 20230T>C (rs2242480), CYP3A4 (rs4646437), CYP3A4 *1B‐392A>G (rs2740574) and CYP3A4 *22 C>T (rs35599367), although the results were less consistent . For instance, the CYP3A4 rs2242480 allele was reported to increase the activity of the CYP3A4 enzyme .…”
mentioning
confidence: 99%
“…9 A number of CYP3A4 polymorphisms were found to affect the expression and activity of CYP3A4 enzyme as well as tacrolimus pharmacokinetics, including CYP3A4 20230T>C (rs2242480), CYP3A4 (rs4646437), CYP3A4*1B-392A>G (rs2740574) and CYP3A4*22 C>T (rs35599367), although the results were less consistent. 10,[14][15][16][17][18] For instance, the CYP3A4 rs2242480 allele was reported to increase the activity of the CYP3A4 enzyme. 19 It can also influence tacrolimus dose-adjusted concentrations in stable kidney transplant recipients.…”
mentioning
confidence: 99%